Green streets, highways, and development 2013, advancing the practice : proceedings of the Second Green Streets, Highways, and Development Conference, November 3-6, 2013, Austin, Texas - Green Streets, Highways, and Development (Conference) (2nd : 2013 : Austin, Tex.); Amekudzi, Adjo A., editor; Otto, Sandra L., editor; Carlson, David J., 1970-, editor; Bomar, Marsha Anderson, editor; Transportation & Development Institute (American Society of Civil Engineers) (Reston, Virginia : American Society of Civil Engineers, 2013)
Includes bibliographical references